Study guides

☆☆

Q: X equals 1 and y equals 6 what is the point of intersection?

Write your answer...

Submit

Still have questions?

Related questions

The intersection is (-2, 6)

x = 5 x-2y = 6 => x = 6+2y 6+2y = 5 2y = 5-6 2y = -1 y = -1/2 and x = 5 Point of intersection: (5, -1/2)

When x = -2 then y = 4 which is the common point of intersection of the two equations.

2X-Y=3 X+Y=3 ---------- 3X = 6 X=2 2(2)-Y=3 4-Y=3 Y=1 Point of interesection: (2,1).

What is the answer for 1+what equals 6

The point of intersection is when a set value of x and y works in both equations - this is a set of simultaneous equations to solve:4y - 2x = 75y - 3x = 65×(1) - 4×(2) → (20y - 20y) + (-10x - -12x) = 35 - 24 → 2x = 11solving (3) gives x = 5.5Substituting for y in (2) gives 5y - 3 × 5.5 = 6 → 5y = 22.5 → y = 4.5Checking by substituting for y and x in (1) gives 4×4.5 - 2×5.5 = 18 - 11 = 7 as required→ the point of intersection of 4y - 2x = 7 and 5y - 3x = 6 is (5.5, 4.5)

Solving the simultaneous equations works out as x = -2 and y = -2 So the lines intersect at: (-2, -2)

If: y = 5x^2 -2x+1 and y = 6-3x-x^2 Then: 5x^2 -2x+1 = 6-3x-x^2 Transposing terms: 6x^2 +x -5 = 0 Factorizing the above: (6x-5)(x+1) = 0 meaning x = 5/6 or x = -1 By substituting the values of x into original equations points of intersection are at (-1, 8) and (5/6, 101/36)

x,y = 5,6 or x = 5 and y = 6

x + y = 6x + y = 2These two equations have no common point (solution).If we graph both equations, we'll find that each one is a straight line.The lines are parallel, and have no intersection point.

x = 1 and y = 6 so the lines intersect at the point (1, 6)

6 divided by 1 equals 6. 6 divided by 6 equals 1.

If: y = 5x^2 -2x +1 and y = 6 -3x -x^2 Then: 5x^2 -2x +1 = 6 -3x -x^2 Transposing terms: 6x^2 +x -5 = 0 Factorizing the above: (6x -5)(x +1) = 0 meaning x = 5/6 or x = -1 By substitution points of intersection are at: (5/6, 101/36) and (-1, 8)

7-1=6

You can work this out by solving one of the equations for either of the variables, and substituting that solution for that variable in the other equation. That will give you one either the X or Y co-ordinate for the point of intersection, and you can calculate the other one with one by plugging that back into one of the original equations: y = x + 4 y = 3x ∴ 3x = x + 4 ∴ 2x = 4 ∴ x = 2 y = 3x ∴ y = 6 So the point of intersection between the lines y = 3x and y = x + 4 is (2, 6).

Straight line equation: y = 2x+10 Perpendicular equation: y = -1/2x+5 Point of intersection: (-2, 6) Distance: the square root of [(2--2)2+(4-6)2] = 4.472 to 3 decimal places

-5

-6

6

1

7 - 6 = 1

-1

6 over 1 equals 6

the answer to 1/3 + 1/6 + 1/6 is 2/3. 1/6 +1/6 equals 2/6 or 1/3 1/3 + 1/3 equals 2/3

1/6 1/3 = 2/6 1/2 = 3/6 therefore 1/6 + 2/6 = 3/6 which equals 1/2